Karakteristik kualitatif tipe penggunaan lahan di zona penyangga Taman Nasional Aketajawe Lolobata - Lis Nurrani; Halidah; Supratman Tabba; Sumarno N. i Patand (Jurnal Penelitian Kehutanan Wallacea, 2012)
Aketajawe Lolobata National Parks is forest conservation designated as protection of flora and fauna endemic to North Maluku. This conservation area sustainability depends greatly on the management and utilization of buffer zone area. This study was conducted to identify types of land use in national parks buffer zone with a focus on Aketajawe region. Sample determination carried out purposive random sampling with a three villages sample, representatives of local communities, migrants and combination of both as the basis for selection of villages. Results showed that land use in this area consists of secondary forest, community forest, mixed garden, monoculture garden, cropping garden, horticulture and paddy field. In the garden area dominated by coconut, cacao, nutmeg and bananas. While other plants are cultivated on the horticulture land such as peppers, tomatoes, watermelon and melon. Farming systems implemented villagers Binagara are more advanced compared to other villages because it was equipped with irrigation facilities and contribute to farmers income continuously.